Análise do conteúdo das matérias sobre expansão universitária veiculadas por jornais de grande circulação no Estado do Ceará no período de 2005-2008 - Costa, Silvia Marta Oliveira (2009)
The university expansion begun during the ‘60s, but it was during the ‘90s that it became highlighted at the educational policies, from the avalanche of growth of the private education. The enlargement process of the Federal Institutes of Superior Education (FISE) begun with the Expand Project, in 2005, which is based in the principle of quantity and quality of the higher education. It got reinforced by the Reuni Program, released in 2007. There are numerous studies about the impacts of the media at individuals behavior. Each individual is able to search and find a media that is compatible with his or hers convictions. The agenda setting hypothesis explains the reach of the media, how they interfere at the everyday matters selection, and how they capture the reality around. The spiral of silence hypothesis refers to the fear of social isolation which make people avoid expressing discordant opinions different from the dominant opinion at the group where they belong. Questions emerged about efficiency and effectiveness of the information published by the newspapers from Ceará about university expansion, the efficiency of the methodology, the possibility of surveying data and the contributions brought from the results of this investigation. The questions that referenced the research were: how the stories about the expansion are conveyed at the newspapers Diário do Nordeste and O Povo? Do these newspapers foment the readers’ participation and do they publish their opinion? Which is their position regarding the public policies at the higher education? The objectives were: analyze the coverage on the issue of expansion at Diário do Nordeste and O Povo from 2005 to 2008, identify the journalistic genres used by Diário do Nordeste and O Povo for the treatment of the subject and analyze the content of the materials disseminated concerning the university expansion in these newspapers. Exploratory study of predominantly qualitative approach, using, for data analysis, the research method of analysis content proposed by Bardin (2004). The results pointed to a coverage with minimal influence on the corpus of knowledge of the citizen, at the discussion of the subject and at the construction of public policies oriented for education. The contents of the subjects printed in the newspapers Diário do Nordeste and O Povo brings us the depoliticization of education as a social issue, capable of an intervention in all spheres, as concerning to media as to the civil society. Communication is a key issue and not merely promotes a divulgation of specific topics with specific subjects, in the case, "education" with the specific subject "university expansion", being necessary to build a new type of relationship among media and citizen, concerning the production of more qualified information and the interface with the society.